Trunk smeared with Haldi - Mumbai Archive Project Team (Jio Institute, 2024)
The trunk is smeared with haldi (turmeric); similar to how a prospective bride is smeared with turmeric during the haldi chadavane (haldi ceremony) before a Koli wedding.